Write a Scientific Paper (WASP) — What can I publish [1]? Types of studies. (February 2019) - Grech, Victor
Abstract: As an experienced writer, one is often asked the question "what can I publish" by younger and inexperienced colleagues who must publish. This paper will briefly review the reasons why academics publish and will then outline what kind of papers one may be able to publish with relative ease, using personal experience and citing first hand material as a practical guide. Potential authors must cultivate "a lean and hungry look" as competition from fellow writers is stiff, and editors are choosy. However, do take heart - if we, older colleagues did and can, you can too.